2007
DOI: 10.1093/geront/47.3.323
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Empowered CNA Teams in Nursing Home Settings: A Longitudinal Assessment

Abstract: As new initiatives strive to move away from the medical model and toward a person-centered model, the data suggest that empowered CNA work teams can help.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 37 publications
2
90
0
Order By: Relevance
“…Coogle, et al (2007) have reported on the positive effects that "enhancement" training (Enhanced Care Assistant Training-ECAT) can have on empowerment and self-esteem. Yeatts and Cready (2007) have described training specifically designed to increase CNA empowerment through the use of empowered work teams. Similarly, Banaszak-Holl and Hines (1996) have concluded that training can allow employees to feel more control over their work (see also Yeatts and Hyten, 1998).…”
Section: Effects Of Training On Cna Attitudesmentioning
confidence: 99%
“…Coogle, et al (2007) have reported on the positive effects that "enhancement" training (Enhanced Care Assistant Training-ECAT) can have on empowerment and self-esteem. Yeatts and Cready (2007) have described training specifically designed to increase CNA empowerment through the use of empowered work teams. Similarly, Banaszak-Holl and Hines (1996) have concluded that training can allow employees to feel more control over their work (see also Yeatts and Hyten, 1998).…”
Section: Effects Of Training On Cna Attitudesmentioning
confidence: 99%
“…The data collection instrument and data for this analysis are extracted from a larger study on employee empowerment in nursing homes; results from the larger study were published by Yeatts and Cready (2007). This larger study was reviewed and approved by the University of North Texas Institutional Review Board.…”
Section: Data Collection Overviewmentioning
confidence: 99%
“…Additional concepts from the family questionnaire included satisfaction with care provided, satisfaction with staff friendliness, and perception of residents choice of bed time, meal time, and shower time (Yeatts & Cready, 2007).…”
Section: Data Collection Overviewmentioning
confidence: 99%
“…8 Research on staff empowerment is still evolving. Using a nonequivalent control, pretest posttest design, Yeatts and Cready 9 showed that em powered teams had a positive impact on the performance of nursing assistants and the families' perceptions of responsiveness to residents' preferences. Other research has shown that empowered staff contribute to an improved quality of life for residents.…”
Section: Staff Empowermentmentioning
confidence: 99%